ADHERENCE TO RESEARCH DATA SHARING PRACTICE IN DENTISTRY OVER THE LAST DECADE: A CROSS-SECTIONAL STUDY - Oliveira, Ana Maria Oliveira (2025)
Objective: This cross-sectional study evaluated the frequency of adherence to sharing dental research data over the last ten years (2013-2023). Methods: Data was obtained by searching the articles published in the five high-impact factor multidisciplinary journals in Dentistry, Oral Surgery & Medicine. A total of 300 dental articles published in three time periods (2013/2018/2023) were randomly selected (n=900). Two researchers performed the study selection and extracted the data. T he main outcome was data sharing (yes/no). Comparative evaluation of data sharing distribution was performed with the Chi-square test and the contribution of variables on the data sharing with adjusted logistic regression. Results: Of the total studies included (n=900), only 20 records reported data sharing practices (data sharing prevalence: 2.2%). A significantly higher prevalence of data sharing was identified among studies published as "open access" [Odds Ratio: 2.97; 95% Confidence Interval: 1.10–8.02], than those published in subscription format. Conclusion: Low adherence to data sharing practices has been identified in the multidisciplinary dental literature. T he results indicated that the type of publication was associated with the outcome, but other aspects, such as the year of publication, continent, and number of citations were not associated with the practice of data sharing.